Faktor-Faktor Yang Mempengaruhi Kualitas Laporan Keuangan - Zalfa Talitha Zulhaninta; Oryza Ardhiarisca (Jurnal Akuntansi dan Keuangan Daerah, 2022)
Every local government agency is obliged to carry out the preparation of regional financial reports. The quality of financial reports is influenced by understanding of accounting and utilization of accounting information systems (AIS). This study aims to analyze the effect of understanding accounting and the use of AIS on the quality of financial reports at the Regional Financial and Asset Management Agency of Jember Regency. The method used in this study is a quantitative method. Data collection is by distributing questionnaires. The determination of respondents is based on certain criteria, namely BPKAD employees who are involved in the preparation of financial statements. From 71 populations, the number of samples in this study was 33 employees. This study was analyzed using multiple linear regression analysis. Based on this research, the results show that there is an influence between the use of AIS and the quality of financial reports, while accounting understanding has no effect on the quality of financial statements